Stunting Coaching Training for Midwives and Cadres about Stunting Prevention and Management in the First 1000 Days of Life - Pardosi, Maida; Hutabarat, Julietta; Surbakti, Elisabeth; Sianturi, Efendi; Pasaribu, Rina Doriana (PT. Riset Press International, 2024)
Stunting is a problem of chronic malnutrition caused by a lack of nutritional intake in the past and a failure to achieve physical development as measured by height for age. This research aims to analyze the effect of stunting coaching training on the knowledge and skills of midwives and cadres. This research was conducted in Tarutung Regency. The research used a quasi-experimental method with a